Quality Improvement Management Based on Partnership and ICT Advantages (Multi Case Study At SMK Muhammadiyah 1 And Smk Ypt 1 Purbalingga Regency) - Efendi, Nafsir; Syamsudidin M., Abin; Wasliman, Iim; Arifin, Daeng (EARR (Educational Administration Research and Review), 2022)
Management was originally a science used in the business world to organize or manage a company. Along with the shift in time and the development of science, management has now penetrated the world of education. Education needs to be managed properly so that education can provide good results in building a complete human being as mandated in the 1945 Constitution.         Education is believed to be the most important aspect in elevating the status of a nation's society. That's why from time to time education is always used as one of the pillars of teachers in improving the quality of a nation. This is because through education the development of knowledge increases so that it can prepare human resources who are ready to compete with all their knowledge and skills.The formation of human resource competencies can be formed through education. Education is part of people's lives and part of the dynamics/movement of society itself, even education for human life is an absolute necessity that must be met throughout life (Fuad Hasan, 2007: 2). When education has been put aside, what happens is very little addition and development of knowledge, so that humans are created who are not ready to compete and will gradually become a backward nation.